Analisis Lahan Pertanian Rawan Banjir Menggunakan Metode Multi Atribut Utility Theory Berbasis Sistem Informasi Geografis - Agung Wijoyo; Muhammad Ashari; Dony Efendi; Muhammad Aqshol Madina (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Abstract-West Java has various regional conditions. The condition of the area certainly has the potential for disasters that have a significant impact on the agricultural sector. Floods are one of the factors that damage agricultural land. Flood risk management plays an important role in guiding the government in making timely and appropriate decisions for flood rescue and relief. This study aims to examine flood risk assessment in the agricultural sector in West Java. The Multi Attribute Utility Theory method is used to solve problems related to spatial planning and disaster management because it is systematic and suitable for solving complex problems such as the agricultural sector. The results showed that the areas of agricultural land in West Java that were highly prone to flooding included Kuningan, Bogor, Tasikmalaya, Sumedang, West Bandung, Bekasi City, Tasikmalaya City, Bogor City, Cimahi City. Furthermore, the results of this study were visualized by mapping flood risk using GIS. This can be used for flood disaster management efforts. This research is expected to help policy making at the Department of Agriculture and Food Security in monitoring agricultural land that is prone to flooding in order to minimize the occurrence of flood disasters in the agricultural sector.